Hypoxic‐induction of arginase II requires EGF‐mediated EGFR activation in human pulmonary microvascular endothelial cells. Issue 10 (20th May 2018) - Pool, Caitlyn M.; Jin, Yi; Chen, Bernadette; Liu, Yusen; Nelin, Leif D.
Abstract: We have previously shown that hypoxia‐induced proliferation of human pulmonary microvascular endothelial cells (hPMVEC) depends on arginase II, and that epidermal growth factor receptor (EGFR) is necessary for hypoxic‐induction of arginase II. However, it remains unclear how hypoxia activates EGFR‐mediated signaling in hPMVEC. We hypothesized that hypoxia results in epidermal growth factor (EGF) production and that EGF binds to EGFR to activate the signaling cascade leading to arginase II induction and proliferation in hPMVEC. We found that hypoxia significantly increased the mRNA levels of EGF, EGFR, and arginase in hPMVEC. Hypoxia significantly increased pEGFR(Tyr845) protein levels and an EGF neutralizing antibody prevented the hypoxic induction of pEGFR. Inhibiting EGFR activation prevented hypoxia‐induced arginase II mRNA and protein induction. Treatment of hPMVEC with exogenous EGF resulted in greater levels of arginase II protein both in normoxia and hypoxia. An EGF neutralizing antibody diminished hypoxic induction of arginase II and resulted in fewer viable cells in hPMVEC. Similarly, siRNA against EGF prevented hypoxic induction of arginase II and resulted in fewer viable cells. Finally, conditioned media from hypoxic hPMVEC induced proliferation in human pulmonary artery smooth muscle cells (hPASMC), however, conditioned media from a group of hypoxic hPMVEC in which EGF were knocked down did not promote hPASMC proliferation. These findings demonstrate that hypoxia‐induced arginase II expression and cellular proliferation depend on autocrine EGF production leading to EGFR activation in hPMVEC. We speculate that EGF‐EGFR signaling may be a novel therapeutic target for pulmonary hypertensive disorders associated with hypoxia. Abstract : These studies demonstrate that EGF is required for the hypoxia‐induced activation of EGFR. Taken together with findings from our previous studies demonstrate that the EGF‐EGFR‐ERK‐arginase II pathway is critical for hypoxia‐induced proliferation in hPMVEC. We speculate that EGF‐EGFR signaling may be a novel therapeutic target for pulmonary hypertensive disorders associated with hypoxia.